Mordecai's magic - Avery, Bryan Patrick (Avery, Bryan Patrick. Mr. Grizley's class., 2022)
It is Mordecai's first day in Mr. Grizley's class, and before he can really introduce himself it is time for the school assembly--but when the scheduled magic show is canceled Mordecai steps in and reveals that he has brought some magic tricks of his own.